EFFECT OF BANK SOUNDNESS LEVEL RGEC METHOD ON INDEX OF FINANCIAL INCLUSIVE IN INDONESIA - Nicola, Daniel; Manalu, Sahala; Hutapea, Tommy Mora Hamonangan (Jurnal Aplikasi Manajemen, 2017)
This study aims to analyze the effect of bank soundness measured by RGEC method on Index of Financial Inclusive (IFI) or weakness of financial service user. The RGEC variables used include NPL, LFR, GCG, ROA, and CAR. sampling research using purposive sampling method. data analysis techniques applied using associative methods with the aim to determine the influence or relationship between two or more variables (Sugiyono, 2012). based on the results of research conducted indicated that NPL and GCG variables have no significant effect on IFI value, but these two ratios basically have been in the standard set by Bank Indonesia. Then LFR, ROA and CAR variables show significant influence on IFI value. of the three influential variables, it is known that ROA is the most influential variable with 65.3% points. the results of this study can be concluded that the Bank Soundness Levelthrough RGEC has an influence on IFI, judging by how much influence in changing the value of IFI.